2022
DOI: 10.1016/j.ijcard.2022.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the local and international stakeholders in rheumatic heart disease field in Tanzania and Uganda: A systematic stakeholder mapping

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…This work will also help identify key areas for future research across sectors, which may encourage further collaboration among national stakeholders in RHD. The results of the proposed systematic review will be published in a peer-reviewed journal, allowing for wider dissemination beyond SA, which will feed into the current information on the profile of RHD in Africa 7 8…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This work will also help identify key areas for future research across sectors, which may encourage further collaboration among national stakeholders in RHD. The results of the proposed systematic review will be published in a peer-reviewed journal, allowing for wider dissemination beyond SA, which will feed into the current information on the profile of RHD in Africa 7 8…”
Section: Discussionmentioning
confidence: 99%
“…As conceptualised by Wyber in 2013,16 this objective will look at 24 of the 25 specific facets of a comprehensive RHD programme, excluding burden of disease (figure 1). The search strategy will be informed by the systematic review protocol published by Moloi et al ,28 which identified stakeholders in RHD in Uganda and Tanzania using a mixed-methods approach that included case series, reports, editorials/commentaries and grey literature 8…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations